A Review of Cluster Head Selection Schemes in Wireless Sensor Network for Energy Efficient Routing Protocol - Tekanyi A.M.S. & Abu-Bilal Kabir Ahmad, Ibrahim Rahman (Covenant Journal of Informatics and Communication Technology, 2019)
Energy management in Wireless Sensor Network (WSN) has attracted much concern due to the fact that the sensors are battery powered, and are usually deployed in hostile and inaccessible environments. With data transmission being the most energy consuming process in the network, several routing protocols based on clustering have been developed for energy efficient data transmission. The challenge of the clustering process in these protocols is the selection of Cluster Heads (CHs). This is due to the use of resource blind random generated number, high cost of network overhead, non-consideration of nodes’ residual energy, and/or location to ensure even distribution of CHs. This paper reviewed energy efficient cluster based routing protocols for WSN and proposed better approaches to mitigate these problems in order to improve network stability and lifetime.